Gum Arabic as fetal hemoglobin inducing agent in sickle cell anemia; in vivo study. Issue 1 (December 2015) - Kaddam, Lamis; FdleAlmula, Imad; Eisawi, Omer; Abdelrazig, Haydar; Elnimeiri, Mustafa; Lang, Florian; Saeed, Amal
Abstract Background High levels of fetal haemoglobin (HbF) decrease sickle cell anaemia (SCA) severity and leads to improved survival. According to in vivo and in vitro studies, butyrate increases HbF production. Its utilization in clinical practice is hampered, however, by its short half-life. Serum butyrate concentrations could be enhanced by colonic bacterial fermentation of Gum Arabic (GA), edible, dried, gummy exudates from Acacia Senegal tree. We hypothesized that regular intake of GA increases serum butyrate levels, thus inducing HbF production and ameliorating symptoms of sickle cell anemia. Methods Fourty seven patients (5–42 years) carrying hemoglobin SS were recruited from April 2014 to January 2015. Patients received 30 g/day GA for 12 weeks. HbF, blood count and erythropoietin level were measured. The main outcome of interest was the level of HbF after 12 weeks. The secondary outcomes were improvement in clinical and laboratory results. The study was ethically approved by Alneelain University IRB. Results The study revealed significant increase in HbF level P.V0.000 [95 % CI, 0.43–1.02], MCV P.V:000 [95 % CI, 2.312–6.058] and Hematocrit level P.V:0.026 [95 % CI, 0.124–1.902]. No significant difference was encountered in platelets count P.V: 0.346 [95 % CI, −25.76–71.94], and WBCs count P.V:0.194 [95 % CI, −8.035–1.68]. Thirty seven percent of patients experienced minor side effects which resolved within a week. Conclusion These findings reveal a novel effect of GA, which may be used to foster fetal hemoglobin production. Trial registration ClinicalTrials.gov Identifier:NCT02467257 . Registered 3rd June 2015.